KONTRIBUSI KOMUNIKASI ANTARPRIBADI DAN KONSEP DIRI TERHADAP KINERJA GURU PESANTREN TERPADU SERAMBI MEKKAH KOTA PADANGPANJANG - Albert Albert (IAIN Batusangkar, 2018)
This study aims to examine the contribution of Inter-Personal Communication and Self- Concept to Teachers' Performance of Integrated Boarding School of Serambi Mekkah of Padang Panjang. The studied variables are Interpersonal Communication and Self Concept as the independent variables and Teachers' Performance as the dependent variable. The respondents of the research are 54 teachers of Integrated Boarding School of Serambi Mekkah of Padang Panjang. The specified sample is 48 people. Sampling is done by using Proportional Sampling technique. Data were collected by questionnaire, then analyzed by using Correlation Analysis and Regression technique to find out its contribution by using partial analysis. The results of the data analysis revealed that: 1) Interpersonal Communication significantly influences the performance of teachers, 2) Self-Concept significantly influences the performance of teachers, and 3) interpersonal communication and self-concept simultaneously , and significantly influences the performance of teachers. From the above findings, it can be concluded that the teachers' interpersonal communication and self-concept are two important factors that can affect the performance of the teacher, despite other factors contribution. Finally, it is recommended to all parties in Integrated Boarding School of Serambi Mekkah of Padang Panjang to give serious attention to both factors above.